Bending rigidity of transition metal dichalcogenide monolayers from first-principles. (6th April 2016) - Lai, Kang; Zhang, Wei-Bing; Zhou, Fa; Zeng, Fan; Tang, Bi-Yu
Abstract: Due to the presence of a sizeable direct band gap, three-atom-thick transition metal dichalcogenide (TMDC) monolayers have been suggested as important candidates for flexible electronic and optoelectronic devices recently. The in-plane elasticity of TMDC monolayers has been investigated extensively, however, little is known about their bending rigidity. Here, we have determined bending rigidities of single-layer MX2 (M = Mo, W; X = S, Se) by fitting the energetics of single wall nanotubes from first-principles to the Helfrich Hamiltonian for the configurational energy of membranes. This parameter-free approach can avoid the controversy induced by ambiguous definition of the thickness of monolayers, which are required in the empirical determination of bending rigidity using classical shell theory. The obtained direction-dependent bending rigidities of single-layer MoS2 are 9.10 and 9.61 eV along the armchair and zigzag directions, which are larger than that estimated using shell theory but similar to the previous analytic formula based on an empirical potential. Moreover, the relative magnitude of bending rigidities for different TMDCs are found to be MoS2 < MoSe2 < WS2 < WSe2, which is in conflict with shell theory. Further analysis indicates that this inconsistence can be understood by a competition mechanism between two-dimensional elastic modulus of monolayers and the structural relaxation of nanotubes.